Cellulose-based ionic liquid bacteriostatic agent as well as preparation method and application thereof

Through freeze-thawing and etherification treatment, the hydrogen bonds of cellulose are destroyed, combined with ionic liquid exchange and plasticizer addition methods, the difficulties of cellulose dissolution and antibacterial materials are solved, and the preparation of low-cost, green and environmentally friendly cellulose-based ionic liquid antibacterial agents are realized, with excellent antibacterial and degradability.

CN119632030APending Publication Date: 2025-03-18ZHEJIANG FORESTRY UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411818239.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The prior art is difficult to achieve cellulose dissolution at low cost and green and environmentally friendly, and the production process of cellulose-based antibacterial materials is complex and difficult to produce and use on a large scale.

Method used

By soluble in alkaline solution and freeze-thawing, the hydrogen bonds of the cellulose are destroyed, and then etherified is carried out to introduce quaternary ammonium cationic groups, increasing the hydrophilic properties of the cellulose. Then ionic liquid is used for ion exchange to improve the degradability of the material, and the toughness and mechanical strength of the material are improved by adding plasticizers, crosslinking agents and reinforcers.

Benefits of technology

The low-cost, green and environmentally friendly dissolution of cellulose is achieved, and a cellulose-based ionic liquid antibacterial agent with excellent antibacterial properties and degradability is prepared. The process is simple and safe.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119632030A_ABST
    Figure CN119632030A_ABST
Patent Text Reader

Abstract

The invention discloses a cellulose-based ionic liquid bacteriostatic agent as well as a preparation method and application thereof, and belongs to the technical field of bacteriostatic materials. The method comprises the following steps: breaking intramolecular and intermolecular hydrogen bonds of cellulose by utilizing freeze thawing treatment to promote rapid dissolution of the cellulose, introducing quaternary ammonium cation groups into a cellulose molecular chain by utilizing etherification treatment, and replacing hydroxyl groups on positions C2, C3 and C6 of glucose units in the cellulose by utilizing reaction groups to break intramolecular or intermolecular hydrogen bonds of the cellulose so as to promote rapid dissolution of the cellulose. The hydrophilic performance of the cellulose is further improved, the ionic liquid exchange reaction in the next step is promoted, and meanwhile, the bacteriostatic function of the cellulose-based ionic liquid bacteriostatic agent can be realized by regulating and controlling the molar weight of the etherifying agent; then ion exchange is carried out by using ionic liquid to improve the degradability of the material, and finally the toughness, mechanical strength and adhesion of the material are further improved by adding a plasticizer, a cross-linking agent and a reinforcing agent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of antibacterial materials, and in particular relates to a cellulose-based ionic liquid antibacterial agent and a preparation method and application thereof. Background Art

[0002] Cellulose is the most abundant natural organic polymer on earth. It has the advantages of being biodegradable, renewable, and recyclable. The rational development and utilization of cellulose-based functional materials can effectively replace non-renewable resources such as coal and oil. However, the disadvantage of cellulose being insoluble in aqueous solutions and most organic solvents limits its application in antibacterial materials and other fields.

[0003] In order to make the functionalization reaction process of cellulose controllable, so as to obtain cellulose-based antibacterial materials with uniform distribution of functional groups and excellent performance, a variety of cellulose dissolution systems have been developed. The traditional cellulose dissolution methods mainly include the copper ammonia method, the viscose method and the acetic acid method. However, these methods are not only expensive, but also pollute the environment and have been gradually eliminated by the market. At present, the most widely used dissolution systems are mainly inorganic dissolution systems and organic dissolution systems. However, organic dissolution systems are usually toxic, difficult to recycle, and have high costs, making them difficult to produce and use on a large scale. Inorganic dissolution systems such as concentrated sulfuric acid, trifluoroacetic acid, and concentrated phosphoric acid can only dissolve cellulose at high concentrations, and have very high requirements for equipment.

[0004] Therefore, how to achieve the dissolution of cellulose in a low-cost, green and environmentally friendly manner with a simple process and obtain a cellulose-based ionic liquid antibacterial agent with excellent antibacterial properties and degradability has become a technical problem that urgently needs to be solved in this field. Summary of the invention

[0005] In order to solve the above technical problems, the present invention proposes a cellulose-based ionic liquid antibacterial agent and a preparation method and application thereof.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] The present invention provides a method for preparing a cellulose-based ionic liquid antibacterial agent, comprising the following steps:

[0008] (1) dissolving cellulose in an alkaline solution and subjecting the solution to freeze-thaw treatment to obtain a cellulose dispersion; subjecting the cellulose dispersion to an etherification treatment and then subjecting the solution to ion exchange with an ionic liquid to obtain an ion-exchanged cellulose solution;

[0009] (2) adding a plasticizer, a cross-linking agent and a reinforcing agent to the cellulose solution after ion exchange obtained in step (1) to obtain a prepolymer solution; polymerizing the prepolymer solution to obtain the cellulose-based ionic liquid antibacterial agent.

[0010] Preferably, in step (1), the amount of cellulose used is 1 to 5 wt % of the total mass of cellulose and alkaline solution.

[0011] Preferably, in step (1), the alkaline solution is a mixed solution containing 4 to 8 wt % of sodium hydroxide and 9 to 14 wt % of urea.

[0012] Preferably, in step (1), the freeze-thaw treatment is performed at a temperature of -60 to -35°C, for a time of 3 to 6 hours, and for 3 to 5 times.

[0013] Preferably, in step (1), the etherifying agent used in the etherification treatment includes 3-chloro-2-hydroxypropyltrimethylammonium chloride; the molar ratio of the 3-chloro-2-hydroxypropyltrimethylammonium chloride to the anhydroglucose unit of cellulose is (1-8):1; the temperature of the etherification treatment is 75-95°C, and the time is 1-4h.

[0014] Preferably, in step (1), the ionic liquid comprises one or more of lithium lactate, potassium lactate and sodium lactate; and the molar ratio of the ionic liquid to the etherifying agent used in the etherification treatment is 1:(1-5).

[0015] Preferably, in step (1), the ion exchange is carried out at a temperature of 50 to 85° C. and for a time of 1 to 5 hours.

[0016] Preferably, in step (2), the amount of the plasticizer is 0.5-2wt% of the mass of the prepolymer liquid; the amount of the cross-linking agent is 0.5-5wt% of the mass of the prepolymer liquid; the amount of the reinforcing agent is 0.5-3wt% of the mass of the prepolymer liquid.

[0017] The present invention provides a cellulose-based ionic liquid antibacterial agent prepared by the preparation method described in the above technical scheme.

[0018] The present invention also provides the use of the cellulose-based ionic liquid antibacterial agent described in the above technical solution as an antibacterial material.

[0019] Compared with the prior art, the present invention has the following advantages and technical effects:

[0020] The invention utilizes freeze-thaw treatment to destroy the hydrogen bonds within and between the molecules of cellulose itself, thereby promoting the rapid dissolution of cellulose, and then utilizes etherification treatment to introduce quaternary ammonium cationic groups into the cellulose molecular chain, and utilizes reactive groups to replace the hydroxyl groups at the C2, C3, and C6 positions of the glucose units in the cellulose, thereby destroying the hydrogen bonds within or between the molecules of the cellulose, further increasing the hydrophilicity of the cellulose, and promoting the next ion liquid exchange reaction. Meanwhile, the antibacterial function of the cellulose-based ionic liquid antibacterial agent can be achieved by regulating the molar amount of the etherifying agent; then, the ionic liquid is utilized to perform ion exchange to improve the degradability of the material, and finally, a plasticizer, a cross-linking agent, and a reinforcing agent are added to further improve the toughness, mechanical strength, and adhesion of the material.

[0021] The preparation method of the invention has the advantages of simple process flow, green environmental protection and safe operation, and the prepared cellulose-based ionic liquid antibacterial agent has excellent antibacterial property and degradability. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:

[0023] Figure 1 This is a scanning electron microscope image of the cross-section interface of the thin-film cellulose-based ionic liquid antibacterial agent prepared in Example 1 adhered to the bamboo material;

[0024] Figure 2 is the tensile strength of the cellulose antibacterial agent prepared in Examples 1 to 3 (a) and Comparative Examples 1 to 3 (b);

[0025] Figure 3 The antibacterial properties of the cellulose-based ionic liquid antibacterial agent prepared in Example 1. DETAILED DESCRIPTION

[0026] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.

[0028] The present invention provides a method for preparing a cellulose-based ionic liquid antibacterial agent, comprising the following steps:

[0029] (1) dissolving cellulose in an alkaline solution and subjecting the solution to freeze-thaw treatment to obtain a cellulose dispersion; subjecting the cellulose dispersion to an etherification treatment and then subjecting the solution to ion exchange with an ionic liquid to obtain an ion-exchanged cellulose solution;

[0030] (2) adding a plasticizer, a cross-linking agent and a reinforcing agent to the cellulose solution after ion exchange obtained in step (1) to obtain a prepolymer solution; polymerizing the prepolymer solution to obtain the cellulose-based ionic liquid antibacterial agent.

[0031] In a preferred embodiment, in step (1), the amount of cellulose used is 1-5wt% of the total mass of cellulose and alkaline solution, preferably 2-5wt%. In the present invention, excessive use of cellulose will lead to reduced dissolution efficiency and solubility. The solubility of cellulose in alkaline solution is limited, and undissolved cellulose is prone to form aggregates that affect subsequent ion exchange and film-forming applications.

[0032] In a preferred embodiment, in step (1), the cellulose is lignocellulose. The present invention uses lignocellulose to prepare the cellulose-based ionic liquid antibacterial agent, which has the advantages of relatively low cost, environmental friendliness, and excellent antibacterial performance.

[0033] In a preferred embodiment, in step (1), the alkaline solution is a mixed solution containing 4-8 wt % of sodium hydroxide and 9-14 wt % of urea.

[0034] In a preferred embodiment, in step (1), the temperature of the freeze-thaw treatment is -60 to -35°C, the time is 3 to 6 hours, and the number of times is 3 to 5 times. The purpose of the freeze-thaw treatment in the present invention is to destroy the intramolecular and intermolecular hydrogen bonds of cellulose itself, and to allow urea to be quickly coated on the outside of the hydrogen bond network of worm-like alkali and cellulose through dynamic self-assembly, forming a urea-alkali-water cluster, which promotes the rapid dissolution of cellulose; controlling the temperature of the freeze-thaw treatment within the above range has the advantages of improving the dissolution efficiency and improving the dispersibility of cellulose. Within the above range, the contact area between cellulose and the solvent can be increased during the freeze-thaw process, and the crystal structure of cellulose may change during this process, so that the intermolecular hydrogen bonds of cellulose are weakened. However, too high a temperature will lead to cellulose degradation, which will lead to a decrease in the molecular weight and degree of polymerization of cellulose. Too low a temperature will increase the viscosity of the solvent, making the mixing and dissolution of cellulose more difficult.

[0035] In a preferred embodiment, in step (1), the etherifying agent used in the etherification treatment includes 3-chloro-2-hydroxypropyltrimethylammonium chloride; the molar ratio of the 3-chloro-2-hydroxypropyltrimethylammonium chloride to the anhydroglucose unit of the cellulose is (1-8):1. The present invention introduces quaternary ammonium cationic groups into the cellulose molecular chain through etherification treatment, and the reactive groups can be used to replace the hydroxyl groups at the C2, C3, and C6 positions of the glucose units in the cellulose to destroy the hydrogen bonds within or between the cellulose molecules, further increase the hydrophilicity of the cellulose, and facilitate the next step of the ion liquid exchange reaction. At the same time, the antibacterial function of the cellulose-based ionic liquid antibacterial agent can be achieved by regulating the molar amount of the cationic etherifying agent 3-chloro-2-hydroxypropyltrimethylammonium chloride.

[0036] In a preferred embodiment, in step (1), the temperature of the etherification treatment is 75-95°C and the time is 1-4 hours. The present invention controls the temperature of the etherification treatment within the above range, which has the advantage of sufficient reaction to obtain cationic cellulose with a high degree of substitution. Too high a temperature will increase side reactions such as decomposition of the etherifying agent and hydrolysis of the product, thereby reducing the degree of substitution of the reaction. Too low a temperature will reduce the reaction rate and incomplete reaction, thereby affecting the uniformity and degree of substitution of the cationic cellulose.

[0037] In a preferred embodiment, in step (1), the ionic liquid comprises one or more of lithium lactate, potassium lactate, and sodium lactate; the molar ratio of the ionic liquid to the etherifying agent used in the etherification treatment is 1:(1-5). When the ionic liquid of the present invention is subjected to ion exchange, lactic acid can combine with the quaternary ammonium cationic groups introduced into the cellulose molecular chain, thereby making the cellulose-based ionic liquid antibacterial agent degradable.

[0038] In a preferred embodiment, in step (1), the ion exchange temperature is 50-85°C and the time is 1-5h. The present invention controls the ion exchange temperature within the above range, which is conducive to increasing the molecular movement speed, thereby increasing the collision efficiency between reactants and improving the degree of ion exchange. If the ion exchange temperature is too high, the product obtained by the etherification treatment will decompose, thereby causing the antibacterial performance to decrease. If the temperature is too low, the ion exchange is insufficient, impurities remain, and the degradation performance will decrease.

[0039] In a preferred embodiment, in step (2), the plasticizer includes glycerol; the crosslinker includes polyvinyl alcohol; and the reinforcing agent includes nanocellulose (CNF). The present invention further improves the toughness, mechanical strength and adhesion of the antibacterial agent by adding plasticizers, crosslinkers and reinforcing agents.

[0040] In a preferred embodiment, in step (2), the amount of the plasticizer is 0.5-2wt% of the mass of the prepolymer liquid, and more preferably 1-2wt%; the amount of the cross-linking agent is 0.5-5wt% of the mass of the prepolymer liquid, and more preferably 2-5wt%; the amount of the reinforcing agent is 0.5-3wt% of the mass of the prepolymer liquid, and more preferably 0.8-3wt%. The present invention controls the amount of the plasticizer, the cross-linking agent and the reinforcing agent within the above range, which is conducive to obtaining a cellulose-based ionic liquid antibacterial agent with high toughness, mechanical strength and adhesion.

[0041] In a preferred embodiment, in step (2), the polymerization is specifically: stirring at room temperature for 2 to 3 hours, and then polymerizing at 65 to 85° C. for 1 to 5 hours.

[0042] The present invention provides a cellulose-based ionic liquid antibacterial agent prepared by the preparation method described in the above technical scheme.

[0043] The present invention also provides the use of the cellulose-based ionic liquid antibacterial agent described in the above technical solution as an antibacterial material.

[0044] The room temperature in the embodiments of the present invention refers to "25±2°C".

[0045] Unless otherwise specified, the raw materials in the examples of the present invention were purchased from commercial sources.

[0046] Example 1

[0047] A method for preparing a cellulose-based ionic liquid antibacterial agent:

[0048] (1) 7 g of NaOH and 12 g of urea were added to 81 mL of water for dissolution to obtain an alkaline solution containing 7 wt% of NaOH and 12 wt% of urea; then, lignocellulose was added to the alkaline solution to prepare a cellulose suspension with a concentration of 3 wt% (the amount of cellulose used was 3 wt% of the total mass of cellulose and the alkaline solution), and the obtained cellulose suspension was subjected to freeze-thaw treatment (-50° C., 3 h) 3 times to obtain a cellulose dispersion; then, 5 g of 3-chloro-2-hydroxypropyltrimethylammonium chloride (the molar ratio of 3-chloro-2-hydroxypropyltrimethylammonium chloride to the anhydroglucose unit of cellulose was 2:1) was added to the cellulose dispersion, reacted at 75° C. for 4 h, cooled to room temperature and neutralized to neutrality, and washed by dialysis to obtain a quaternized cellulose liquid;

[0049] (2) taking 25 g of the quaternized cellulose liquid obtained in step (1) into a beaker, then adding 1.2 g of lithium lactate (the molar ratio of lithium lactate to 3-chloro-2-hydroxypropyltrimethylammonium chloride is 1:1.56), reacting at 75° C. for 4 h, and dialysis washing to obtain an ion-exchanged cellulose solution;

[0050] (3) Adding glycerol, polyvinyl alcohol and nanofibers (CNF) to the ion-exchanged cellulose solution obtained in step (2) to prepare a prepolymer solution, wherein the concentration of glycerol in the prepolymer solution is 1 wt%, the concentration of polyvinyl alcohol is 5 wt%, and the concentration of nanocellulose (CNF) is 3 wt%; stirring the obtained prepolymer solution at room temperature for 2 h, and then transferring it to a mold and polymerizing it at 65° C. for 5 h to obtain a thin film of cellulose-based ionic liquid antibacterial agent.

[0051] Figure 1 This is a scanning electron microscope image of the cross-section of the thin film cellulose-based ionic liquid antibacterial agent prepared in Example 1 adhered to the bamboo. Figure 1 It can be seen that the cellulose-based ionic liquid antibacterial film has excellent adhesion and can form a mutually adherent structure with the substrate.

[0052] Example 2

[0053] (1) 6 g of NaOH and 14 g of urea are added to 80 mL of water for dissolution to obtain an alkaline solution containing 6 wt% of NaOH and 14 wt% of urea; then, lignocellulose is added to the alkaline solution to prepare a cellulose suspension with a concentration of 5 wt% (the amount of cellulose used is 5 wt% of the total mass of cellulose and the alkaline solution), and the obtained cellulose suspension is subjected to freeze-thaw treatment (-40° C., 5 h) 3 times to obtain a cellulose dispersion; then, 9 g of 3-chloro-2-hydroxypropyltrimethylammonium chloride (the molar ratio of 3-chloro-2-hydroxypropyltrimethylammonium chloride to the anhydroglucose unit of cellulose is 2:1) is added to the cellulose dispersion, reacted at 90° C. for 2 h, cooled to room temperature, neutralized to neutrality, and dialyzed and washed to obtain a quaternized cellulose liquid;

[0054] (2) taking 25 g of the quaternized cellulose liquid obtained in step (1) into a beaker, then adding 3.2 g of lithium lactate (the molar ratio of lithium lactate to 3-chloro-2-hydroxypropyltrimethylammonium chloride is 1:1), reacting at 85° C. for 5 h, and dialysis washing to obtain an ion-exchanged cellulose solution;

[0055] (3) Adding glycerol, polyvinyl alcohol and nanofibers (CNF) to the ion-exchanged cellulose solution obtained in step (2) to prepare a prepolymer solution, wherein the concentration of glycerol in the prepolymer solution is 0.8wt%, the concentration of polyvinyl alcohol is 1wt%, and the concentration of nanocellulose (CNF) is 0.8wt%; stirring the obtained prepolymer solution at room temperature for 3h, and then transferring it to a mold and polymerizing it at 75°C for 2h to obtain a cellulose-based ionic liquid antibacterial agent.

[0056] Example 3

[0057] A method for preparing a cellulose-based ionic liquid antibacterial agent:

[0058] (1) 8 g of NaOH and 11 g of urea are added to 81 mL of water for dissolution to obtain an alkaline solution containing 8 wt % of NaOH and 11 wt % of urea; then, lignocellulose is added to the alkaline solution to prepare a cellulose suspension with a concentration of 2 wt % (the amount of cellulose used is 2 wt % of the total mass of cellulose and the alkaline solution), and the obtained cellulose suspension is subjected to freeze-thaw treatment (-60° C., 6 h) 5 times to obtain a cellulose dispersion; then, 15 g of 3-chloro-2-hydroxypropyltrimethylammonium chloride (the molar ratio of 3-chloro-2-hydroxypropyltrimethylammonium chloride to the anhydroglucose unit of cellulose is 8:1) is added to the cellulose dispersion, reacted at 95° C. for 1 h, cooled to room temperature, neutralized to neutrality, and dialyzed and washed to obtain a quaternized cellulose liquid;

[0059] (2) taking 25 g of the quaternized cellulose liquid obtained in step (1) into a beaker, then adding 5 g of lithium lactate (the molar ratio of lithium lactate to 3-chloro-2-hydroxypropyltrimethylammonium chloride is 1:1), reacting at 85° C. for 5 h, and dialysis washing to obtain an ion-exchanged cellulose solution;

[0060] (3) Adding glycerol, polyvinyl alcohol and nanofibers (CNF) to the ion-exchanged cellulose solution obtained in step (2) to prepare a prepolymer solution, wherein the concentration of glycerol, the concentration of polyvinyl alcohol and the concentration of nanocellulose (CNF) are 2 wt %; stirring the obtained prepolymer solution at room temperature for 3 h, and then transferring it to a mold and polymerizing it at 85° C. for 1 h to obtain a cellulose-based ionic liquid antibacterial agent.

[0061] Comparative Example 1

[0062] The difference from Example 1 is that the glycerol in step (3) is omitted, and the rest is the same as Example 1.

[0063] Comparative Example 2

[0064] The difference from Example 1 is that in step (3), the concentration of polyvinyl alcohol in the prepolymer solution is 7 wt %. The rest is the same as Example 1.

[0065] Comparative Example 3

[0066] The difference from Example 1 is that the concentration of nanocellulose (CNF) in the prepolymer solution in step (3) is 5 wt %. The rest is the same as Example 1.

[0067] Performance Testing

[0068] The mechanical properties of the cellulose antibacterial agents prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were tested respectively. The specific method was as follows: the cellulose antibacterial agents prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were made into 20 mm × 15 mm I-shaped specimens, and then the prepared I-shaped specimens were installed on a TS20000-S multifunctional material testing machine, the tensile speed of the testing machine was set to 50 mm / min, the load was applied, the tensile test was started, the stress-elongation curve of the film during the stretching process was recorded, and finally when the specimen broke, the maximum load value and the corresponding elongation were recorded; the tensile strength was calculated as P = F / S, wherein P is the tensile strength of the specimen (MPa), F is the load applied when the specimen broke (N), and S is the cross-sectional area of ​​the specimen before testing (mm 2 ), test results see Figure 2 , Figure 2 The stress in is the tensile strength.

[0069] Figure 2 is the tensile strength of the cellulose antibacterial agent prepared in Examples 1 to 3 and Comparative Examples 1 to 3, wherein a is the tensile strength of the cellulose antibacterial agent prepared in Examples 1 to 3, and b is the tensile strength of the cellulose antibacterial agent prepared in Comparative Examples 1 to 3. Figure 2 It can be seen that the maximum tensile strength of the cellulose-based ionic liquid antibacterial agent prepared by Examples 1 to 3 is 11 MPa; while the maximum tensile strength of the cellulose-based ionic liquid antibacterial agent prepared by Comparative Examples 1 to 3 is only 7.3 MPa, indicating that the cellulose-based ionic liquid antibacterial agent prepared by Examples 1 to 3 has better tensile strength.

[0070] The cellulose-based ionic liquid antibacterial agent prepared in Example 1 was dripped onto an agar plate and cultured at 37°C for 6 h. The number of colonies formed at each dripping point was counted to obtain the antibacterial performance of the sample against the test strain. The results are shown in Figure 3 .

[0071] Figure 3 The antibacterial properties of the cellulose-based ionic liquid antibacterial agent prepared in Example 1. Figure 3 It can be calculated that the antibacterial rates of the antibacterial agent against Escherichia coli and Staphylococcus aureus are 95.52% and 92.21% respectively, both of which have good antibacterial properties, but the antibacterial effect on Escherichia coli is better.

[0072] The above are only preferred specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A method for preparing a cellulose-based ionic liquid antibacterial agent, characterized in that: The following steps are involved: (1) dissolving cellulose in an alkaline solution and subjecting the solution to freeze-thaw treatment to obtain a cellulose dispersion; subjecting the cellulose dispersion to an etherification treatment and then subjecting the solution to ion exchange with an ionic liquid to obtain an ion-exchanged cellulose solution; (2) adding a plasticizer, a crosslinking agent and a reinforcing agent to the cellulose solution after ion exchange obtained in step (1) to obtain a prepolymer solution; The prepolymer solution is polymerized to obtain the cellulose-based ionic liquid antibacterial agent.

2. The preparation method according to claim 1, characterized in that: In step (1), the amount of cellulose used is 1 to 5 wt % of the total mass of cellulose and alkaline solution.

3. The preparation method according to claim 1, characterized in that: In step (1), the alkaline solution is a mixed solution containing 4-8wt% sodium hydroxide and 9-14wt% urea.

4. The preparation method according to claim 1, characterized in that: In step (1), the freeze-thaw treatment is performed at a temperature of -60 to -35°C, for a time of 3 to 6 hours, and for 3 to 5 times.

5. The preparation method according to claim 1, characterized in that: In step (1), the etherifying agent used in the etherification treatment includes 3-chloro-2-hydroxypropyltrimethylammonium chloride; the molar ratio of the 3-chloro-2-hydroxypropyltrimethylammonium chloride to the anhydroglucose unit of the cellulose is (1-8):1; the temperature of the etherification treatment is 75-95°C, and the time is 1-4h.

6. The preparation method according to claim 1, characterized in that: In step (1), the ionic liquid includes one or more of lithium lactate, potassium lactate, and sodium lactate; the molar ratio of the ionic liquid to the etherifying agent used in the etherification treatment is 1:(1-5).

7. The preparation method according to claim 1, characterized in that: In step (1), the ion exchange temperature is 50 to 85° C. and the time is 1 to 5 hours.

8. The preparation method according to claim 1, characterized in that: In step (2), the amount of the plasticizer is 0.5-2wt% of the mass of the prepolymer liquid; the amount of the cross-linking agent is 0.5-5wt% of the mass of the prepolymer liquid; the amount of the reinforcing agent is 0.5-3wt% of the mass of the prepolymer liquid.

9. A cellulose-based ionic liquid antibacterial agent prepared according to the preparation method according to any one of claims 1 to 8.

10. Use of the cellulose-based ionic liquid antibacterial agent according to claim 9 as an antibacterial material.